2022
DOI: 10.3389/fenrg.2022.872959
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Thermochemical CO2 Splitting Using Partially-Substituted Perovskite Oxides of La0.7Sr0.3Mn0.9X0.1O3 for Solar Fuel Production

Abstract: We investigated, herein, the redox activity of partial substitution of the B-site in a series of lanthanum/strontium-manganese-based (LSM) perovskite oxide, La0.7Sr0.3Mn0.9X0.1O3 for solar two-step thermochemical fuel production using concentrated solar radiation as an energy source. We systematically investigated the effects of partial substitution in LaSrMnO3 in terms of their kinetics behavior, oxygen/CO productivity, thermal reduction/oxidation temperatures. Furthermore, repeatability was evaluated and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 80 publications
0
0
0
Order By: Relevance
“…Compared to the valence change of the Mn ions in the nonsubstituted sample, the valence change increased in the LSMCo0.35 sample. The result of the LSMCo0.35 sample agreed well with the result of the 10%Mg-substituted sample without a valence change in Mg in a previous study [53]. Table 6.…”
Section: Xps Analysis Of Nonsubstituted- Ni- and Co-substituted Lsmssupporting
confidence: 89%
See 4 more Smart Citations
“…Compared to the valence change of the Mn ions in the nonsubstituted sample, the valence change increased in the LSMCo0.35 sample. The result of the LSMCo0.35 sample agreed well with the result of the 10%Mg-substituted sample without a valence change in Mg in a previous study [53]. Table 6.…”
Section: Xps Analysis Of Nonsubstituted- Ni- and Co-substituted Lsmssupporting
confidence: 89%
“…The best-performing samples in this study ranked at the highest level of both CO productivities compared to the reported substituted LSMs, where LSMCo0.35 exhibited the maximum CO productivity (533 µmol/g material) among the reported LSM perovskites. Compared to the authors' previous results marked with a triangle (LSMMg0.10, LSMCo0.10, and LSMNi0.10) [53], obtained under the same test conditions using the same methods and devices, the CO productivity of LSMCo0.35 was ~1.5 times higher. Other perovskite materials that are not LSM series, Sm 0.6 Ca 0.4 Mn 0.8 Al 0.20 O 3 [68], Sr 0.6 Ce 0.4 Mn 0.8 Al 0.2 O 3 [69], and Sm 0.6 Sr 0.4 MnO 3 [70], were studied for the thermochemical two-step CO 2 splitting cycle.…”
Section: Xps Analysis Of Nonsubstituted- Ni- and Co-substituted Lsmscontrasting
confidence: 65%
See 3 more Smart Citations